Analysis Of Factors Affecting Land Value (Case Study In Sub-District Medan Timur Medan City) - Irwan Bogie; Moehammad Nawawiy Loebis; Nazaruddin Matondang; Sheila Hani (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to determine the factors that affect the value of land in the District of Medan Timur Medan. LT, JTF, AE, LEG, ETN are 5 (five) variables that are used as factors that affect the value of land in Medan Timur Sub – District. The data used are primary data, sampling technique used is Propostionate Stratified Random Sampling. The results showed that the factors LT, JTF, AE, LEG, ETN positive and significant effect, variable economic activity (AE) with a Standardized coefficient of 0.269 has the most dominant influence on the value of land compared to other variables. Land value Model with regression analysis techniques that can be used in the District of Medan East Medan city is Y = 3.297 + 1.241 (LT) + 0.885 (JTF) + 1.325 (AE) + 1.755 (LEG) + 2.608 (ETN), while the Standard Error of the Estimate of 3.73091